Two Case Studies in Local Cable Renewal - Burns, George (Maine Policy Review, 1993)
In October, 1992, Congress responded to consumer complaints about their cable rates and services by passing the Cable Television Consumer Protection and Competition Act of 1992. The numerous provisions of the new act were the subject of two, day-long workshops held in Portland and Orono last fall that were targeted to municipal officials. The workshops were jointly sponsored by the Margaret Chase Smith Center for Public Policy, the Maine Municipal Association and the Community Television Network of Portland. Three articles in this issue are excerpted from those presentations in an effort to both communicate and explain the important changes wrought by the new cable act. Portland attorney George Burns describes two of his experiences with local cable franchise renewals.